FINDS OF THE CLASSICAL PERIOD AT OGLANKALA - Tahirli, Ayten (International Journal of Innovative Technologies in Social Science, 2023)
Studies show that the settlement of Oglankala, located in the north-east of the Sharur region of Azerbaijan, was inhabited in different periods of history. The strata of this settlement reflect various periods of the Iron Age. Despite the fact that research on the territory of Nakhchivan revealed finds relating to various periods of the Iron Age, however, the classical period has been studied very little. In this regard, architectural remains and other finds of the classical period, revealed by excavations of the Oglankala settlement, are of importance. Archaeological excavations carried out by the Azerbaijan-USA joint expedition in 2008-2011 showed that the citadel and its environs were inhabited in the Oglankala settlement in the classical period. The finds found in Oglankala show that a center for local authority was built here, and after the campaign of the Alexander Great, great construction work was carried out on the settlement. During the excavations, remains of architectural remains, and especially the remains of a columned hall and pottery belonging to various stages of the classical period, were revealed. Cultural strata of Oglankala dating back to the 4th-1st centuries BC are important for studying the history of the Middle East, the South Caucasus, including Nakhchivan.